Westonci.ca is your go-to source for answers, with a community ready to provide accurate and timely information. Our Q&A platform provides quick and trustworthy answers to your questions from experienced professionals in different areas of expertise. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
Let's solve the problem step-by-step.
We are given:
[tex]\[ \cos A = \frac{1}{2} \][/tex]
[tex]\[ \cos B = \frac{\sqrt{3}}{2} \][/tex]
First, we'll calculate [tex]\( \sin A \)[/tex] and [tex]\( \sin B \)[/tex] using the Pythagorean identity:
[tex]\[ \sin^2 A + \cos^2 A = 1 \][/tex]
[tex]\[ \sin^2 B + \cos^2 B = 1 \][/tex]
### Calculating [tex]\( \sin A \)[/tex]:
[tex]\[ \begin{align*} \cos^2 A &= \left( \frac{1}{2} \right)^2 \\ &= \frac{1}{4} \end{align*} \][/tex]
[tex]\[ \begin{align*} \sin^2 A &= 1 - \cos^2 A \\ &= 1 - \frac{1}{4} \\ &= \frac{3}{4} \end{align*} \][/tex]
[tex]\[ \sin A = \sqrt{\frac{3}{4}} = \frac{\sqrt{3}}{2} \][/tex]
### Calculating [tex]\( \sin B \)[/tex]:
[tex]\[ \begin{align*} \cos^2 B &= \left( \frac{\sqrt{3}}{2} \right)^2 \\ &= \frac{3}{4} \end{align*} \][/tex]
[tex]\[ \begin{align*} \sin^2 B &= 1 - \cos^2 B \\ &= 1 - \frac{3}{4} \\ &= \frac{1}{4} \end{align*} \][/tex]
[tex]\[ \sin B = \sqrt{\frac{1}{4}} = \frac{1}{2} \][/tex]
### Calculating [tex]\( \cos(A + B) \)[/tex]:
Using the angle addition formula for cosine:
[tex]\[ \cos(A + B) = \cos A \cos B - \sin A \sin B \][/tex]
[tex]\[ \cos A = \frac{1}{2}, \quad \cos B = \frac{\sqrt{3}}{2}, \quad \sin A = \frac{\sqrt{3}}{2}, \quad \sin B = \frac{1}{2} \][/tex]
[tex]\[ \begin{align*} \cos(A + B) &= \left( \frac{1}{2} \times \frac{\sqrt{3}}{2} \right) - \left( \frac{\sqrt{3}}{2} \times \frac{1}{2} \right) \\ &= \left( \frac{\sqrt{3}}{4} \right) - \left( \frac{\sqrt{3}}{4} \right) \\ &= \frac{\sqrt{3}}{4} - \frac{\sqrt{3}}{4} \\ &= 0 \end{align*} \][/tex]
So the value of [tex]\( \cos(A + B) \)[/tex] is [tex]\( 0 \)[/tex].
The correct answer is (a) 0.
We are given:
[tex]\[ \cos A = \frac{1}{2} \][/tex]
[tex]\[ \cos B = \frac{\sqrt{3}}{2} \][/tex]
First, we'll calculate [tex]\( \sin A \)[/tex] and [tex]\( \sin B \)[/tex] using the Pythagorean identity:
[tex]\[ \sin^2 A + \cos^2 A = 1 \][/tex]
[tex]\[ \sin^2 B + \cos^2 B = 1 \][/tex]
### Calculating [tex]\( \sin A \)[/tex]:
[tex]\[ \begin{align*} \cos^2 A &= \left( \frac{1}{2} \right)^2 \\ &= \frac{1}{4} \end{align*} \][/tex]
[tex]\[ \begin{align*} \sin^2 A &= 1 - \cos^2 A \\ &= 1 - \frac{1}{4} \\ &= \frac{3}{4} \end{align*} \][/tex]
[tex]\[ \sin A = \sqrt{\frac{3}{4}} = \frac{\sqrt{3}}{2} \][/tex]
### Calculating [tex]\( \sin B \)[/tex]:
[tex]\[ \begin{align*} \cos^2 B &= \left( \frac{\sqrt{3}}{2} \right)^2 \\ &= \frac{3}{4} \end{align*} \][/tex]
[tex]\[ \begin{align*} \sin^2 B &= 1 - \cos^2 B \\ &= 1 - \frac{3}{4} \\ &= \frac{1}{4} \end{align*} \][/tex]
[tex]\[ \sin B = \sqrt{\frac{1}{4}} = \frac{1}{2} \][/tex]
### Calculating [tex]\( \cos(A + B) \)[/tex]:
Using the angle addition formula for cosine:
[tex]\[ \cos(A + B) = \cos A \cos B - \sin A \sin B \][/tex]
[tex]\[ \cos A = \frac{1}{2}, \quad \cos B = \frac{\sqrt{3}}{2}, \quad \sin A = \frac{\sqrt{3}}{2}, \quad \sin B = \frac{1}{2} \][/tex]
[tex]\[ \begin{align*} \cos(A + B) &= \left( \frac{1}{2} \times \frac{\sqrt{3}}{2} \right) - \left( \frac{\sqrt{3}}{2} \times \frac{1}{2} \right) \\ &= \left( \frac{\sqrt{3}}{4} \right) - \left( \frac{\sqrt{3}}{4} \right) \\ &= \frac{\sqrt{3}}{4} - \frac{\sqrt{3}}{4} \\ &= 0 \end{align*} \][/tex]
So the value of [tex]\( \cos(A + B) \)[/tex] is [tex]\( 0 \)[/tex].
The correct answer is (a) 0.
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. We hope this was helpful. Please come back whenever you need more information or answers to your queries. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.